2022
DOI: 10.1136/jcp-2022-208625
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an ISO15189 accredited next-generation sequencing service with the fully automated Ion Torrent Genexus: the experience of a clinical diagnostic laboratory

Abstract: AimsNext-generation sequencing (NGS) is integral to the delivery of personalised medicine for targeted cancer therapy. Average turnaround times (TAT) from reference laboratories with advanced expertise in sequencing are typically 2–3 weeks. Prolonged TAT for biomarker analysis can adversely affect patient outcomes. The project aim was to establish an accredited NGS service integrated within a routine clinical diagnostic laboratory, in a designated tertiary cancer centre with no previous experience in NGS or bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Additionally, a study using cell-free DNA from non-small cell lung cancer demonstrated that Genexus is a fully automated and highly accurate NGS system with a short turnaround time [14]. This suggests that the Genexus system can provide accurate identi cation of tumor markers for oncology research with a fast turnaround, be implemented in a hospital laboratory, and help clinicians make timely decision for the oncologist [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study using cell-free DNA from non-small cell lung cancer demonstrated that Genexus is a fully automated and highly accurate NGS system with a short turnaround time [14]. This suggests that the Genexus system can provide accurate identi cation of tumor markers for oncology research with a fast turnaround, be implemented in a hospital laboratory, and help clinicians make timely decision for the oncologist [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, Genexus requires only a few steps: setting up a run with a few iterations of pipetting, and then loading all the pre lled reagents and consumables according to the instructions on the sequencer's touchscreen. Genexus has the potential to establish NGS services within a routine clinical diagnostic laboratory, even in a regional hospital with no previous experience with NGS [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the type of cancer tested and the type of panel used to assess TMB can significantly affect the outcome ( Merino et al, 2020 ). Among the many examples of targeted panels used in the clinical setting there are MyeloSeq, a 40-gene targeted panel used to determine variant and allele frequencies in patients with suspected hematologic malignancies ( Barnell et al, 2021 ), the Oncomine Precision Assay, which tests 45 cancer-related genes (such as EGFR, KRAS, ALK, RET, BRAF, and others) used in screening for genomic alterations that can be treated with targeted therapy in NSCLC, colorectal cancer, melanoma, breast cancer, and other malignancies ( Werner et al, 2022 ; Nindra et al, 2023 ), and other targeted panels such as the TruSight Oncology, the AmpliSeq, the FusionPlex, the QIASeq Multimodal Lung, which have demonstrated expertise in identifying genetic variants, and the NTRK gene fusion panel used to identify tumors sensitive to larotrectinib, an NTRK inhibitor ( Drilon et al, 2018 ; Stockley et al, 2023 ).…”
Section: Ngs Approachesmentioning
confidence: 99%
“…The Ion Torrent Genexus has previously been accredited to ISO 15189 with formalin-fixed paraffin-embedded (FFPE) tissue. 42 The Genexus may also be used for cfTNA isolated from plasma without requiring a high level of user expertise in bioinformatics and reporting. 43 It facilitates a minimal nucleic acid input volume of approximately 5 ng, with run sizes of 1-5 cfTNA samples, using a cost per assay instead of a cost per run model.…”
Section: Objectivesmentioning
confidence: 99%
“…Data collated from the Genexus software enabled the generation of performance metrics, similar to quality parameters established previously for tissue NGS on the Genexus. 42 These internal quality control checks determine which findings are released when curating reports (table 2). Importantly, the mapped reads for the DNA library according to manufacturer specifications should be between 8 and 12 million reads per sample.…”
Section: Sequencing Performancementioning
confidence: 99%